Patterns of Neck Nodal Metastasis from Oral Cavity Carcinoma - Nitin Khunteta; Ayush Makkar; Jaspreet Singh Badwal; Prakhar Katta; Dinesh Choudhary; Mohinder Viswanath; Hemant Malhotra (South Asian Journal of Cancer, 2022)
Abstract